Pola Sensitivitas Isolat Klinis Bakteri Gram Negatif Multiresisten Obat Terhadap Fosfomisin dari Beberapa Rumah Sakit Kota Pekanbaru - Dewi Anggraini; Atya Nasmah; Fauzia Andrini (Fakultas Kedokteran Universitas Riau, 2019)
Over the last few years, there has been a decrease in amount of effective antibiotics, coincide with the lack of new antibiotics relevant for the treatment of Gram negative multi-drug resistant organisms infections. This problem can be overcome by the assessment and re-introduction of old antibiotics such as fosfomycin. Fosfomycin is a broad spectrum antibiotic that is bactericidal. This study aimed to find out the sensitivity pattern of clinical isolate multi-drug resistant Gram negative bacteria to fosfomycin with descriptive cross sectional method. The sample used in this study was clinical isolates collection of Microbiology Laboratory Faculty of Medicine, University of Riau from Hospitals in Pekanbaru. The result showedsensitivity to fosfomycin Escherichia coli producing ESBL (88%), Klebsiella pneumoniae producing ESBL (95%), Acinotobacter baumannii resistant meropenem (27%), Pseudomonas aeruginosa resistant meropenem (36%) and K.pneumoniae resistant meropenem (70%). Fosfomycin can be used as alternative therapy for infections caused by Gram-negative Multi-drug resistant organisms.